microRNA Expression in the Late Embryonic Pax6-Null Mouse Cerebellum - Ayasha Abdalla-Wyse; Yuliya Badayeva; Daniel Goldowitz; Maryam Rahimi-Balaei (Molecular Neurobiology, 2026)

Conference Report: Cerebellar Development and Disease at Single-Cell Resolution - Lena M. Kutscher; Davide Aprile; N. Sumru Bayin; Esther B. E. Becker; Valentina Cerrato; Giacomo Turrini; Marion Coolen; Vincent Cantagrel; Béatrice C. Durand; Myron K. Evans II; Parthiv Haldipur; Kathleen J. Millen; et al. (The Cerebellum, 2025)

Cerebellum Lecture: the Cerebellar Nuclei—Core of the Cerebellum - Justus M. Kebschull; Filippo Casoni; G. Giacomo Consalez; Daniel Goldowitz; Richard Hawkes; Tom J. H. Ruigrok; Karl Schilling; Richard Wingate; Joshua Wu; Joanna Yeung; Marylka Yoe Uusisaari (The Cerebellum, 2023)
The cerebellum is a key player in many brain functions and a major topic of neuroscience research. However, the cerebellar nuclei (CN), the main output structures of the cerebellum, are often overlooked. This neglect is because research on the cerebellum typically focuses on the cortex and tends to treat the CN as relatively simple output nuclei conveying an inverted signal from the cerebellar cortex to the rest of the brain. In this review, by adopting a nucleocentric perspective we aim to rectify this impression. First, we describe CN anatomy and modularity and comprehensively integrate CN architecture with its highly organized but complex afferent and efferent connectivity. This is followed by a novel classification of the specific neuronal classes the CN comprise and speculate on the implications of CN structure and physiology for our understanding of adult cerebellar function. Based on this thorough review of the adult literature we provide a comprehensive overview of CN embryonic development and, by comparing cerebellar structures in various chordate clades, propose an interpretation of CN evolution. Despite their critical importance in cerebellar function, from a clinical perspective intriguingly few, if any, neurological disorders appear to primarily affect the CN. To highlight this curious anomaly, and encourage future nucleocentric interpretations, we build on our review to provide a brief overview of the various syndromes in which the CN are currently implicated. Finally, we summarize the specific perspectives that a nucleocentric view of the cerebellum brings, move major outstanding issues in CN biology to the limelight, and provide a roadmap to the key questions that need to be answered in order to create a comprehensive integrated model of CN structure, function, development, and evolution.

The Cerebellar Gene Database: a Collective Database of Genes Critical for Cerebellar Development - Miguel Ramirez; Joshua Wu; Matthew Liu; Derek Wu; Dave Weeden; Daniel Goldowitz (The Cerebellum, 2022)
This report presents the first comprehensive database that specifically compiles genes critical for cerebellar development and function. The Cerebellar Gene Database details genes that, when perturbed in mouse models, result in a cerebellar phenotype according to available data from both Mouse Genome Informatics and PubMed, as well as references to the corresponding studies for further examination. This database also offers a compilation of human genetic disorders with a cerebellar phenotype and their associated gene information from the Online Mendelian Inheritance in Man (OMIM) database. By comparing and contrasting the mouse and human datasets, we observe that only a small proportion of human mutant genes with a cerebellar phenotype have been studied in mouse knockout models. Given the highly conserved nature between mouse and human genomes, this surprising finding highlights how mouse genetic models can be more frequently employed to elucidate human disease etiology. On the other hand, many mouse genes identified in the present study that are known to lead to a cerebellar phenotype when perturbed have not yet been found to be pathogenic in the cerebellum of humans. This database furthers our understanding of human cerebellar disorders with yet-to-be-identified genetic causes. It is our hope that this gene database will serve as an invaluable tool for gathering background information, generating hypotheses, and facilitating translational research endeavors. Moreover, we encourage continual inputs from the research community in making this compilation a living database, one that remains up-to-date with the advances in cerebellar research.

Systems genetics of intravenous cocaine self-administration in the BXD recombinant inbred mouse panel - Price E. Dickson; Mellessa M. Miller; Michele A. Calton; Jason A. Bubier; Melloni N. Cook; Daniel Goldowitz; Elissa J. Chesler; Guy Mittleman (Psychopharmacology, 2016)

The genetic basis of adrenal gland weight and structure in BXD recombinant inbred mice - Domenico L. Di Curzio; Daniel Goldowitz (Mammalian Genome, 2011)

A deletion causing spontaneous fracture identified from a candidate region of mouse Chromosome 14 - Yan Jiao; Xinmin Li; Wesley G. Beamer; Jian Yan; Yiai Tong; Daniel Goldowitz; Bruce Roe; Weikuan Gu (Mammalian Genome, 2005)

Implementing Large-Scale ENU Mutagenesis Screens in North America - Amander T. Clark; Daniel Goldowitz; Joseph S. Takahashi; Martha Hotz Vitaterna; Sandra M. Siepka; Luanne L. Peters; Wayne N. Frankel; George A. Carlson; Janet Rossant; Joseph H. Nadeau; Monica J. Justice (Genetica, 2004)